2018
DOI: 10.33369/jeet.2.2.1-8
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Code Mixing in a Debate Activity as Part of English Club Programs at Sman 2 Bengkulu City

Abstract: The aim of this research is to investigate code mixing produced by the students of ‘Debate Activity as part of English Club’ program at SMAN 2 Bengkulu city. The design are descriptive quantitative and qualitative. The subject is eight students who are involved in the debate activity. The instruments consist of observation checklist and interview. The data are taken from the recording of the debate activity on 18th May 2018. In analyzing the data, the researcher trancribes the recording, classifies the data wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Bilingual or multilingual people can use code-mixing (CM) and code-switching (CS) more often. Many scholars explore the phenomenon of CM and CS in many contexts and situations, such as educational context (Alkhawaldeh, 2019;Alkhresheh, 2015;Hayek, 2016;Kustati, 2014;Susylowati, Sumarlam, Abdullah, & Marmanto, 2019;Zetri, Arasuli, & Aziz, 2018), Islamic religious discourse (Bassiouney, 2013;Ismail, 2015;Stille, 2018;Susanto, 2006;Syam & Fitrawati, 2020;Triana & Eka Saputra, 2018), Christian discourse (Dladla, 2017), media (Octaviana, 2019;Silaban & Marpaung, 2020;Sutrisno & Ariesta, 2019), and leaders' discourse (Purba, 2017;Sugiantari, 2018;Wibowo et al, 2017).…”
Section: Background Of Studymentioning
confidence: 99%
“…Bilingual or multilingual people can use code-mixing (CM) and code-switching (CS) more often. Many scholars explore the phenomenon of CM and CS in many contexts and situations, such as educational context (Alkhawaldeh, 2019;Alkhresheh, 2015;Hayek, 2016;Kustati, 2014;Susylowati, Sumarlam, Abdullah, & Marmanto, 2019;Zetri, Arasuli, & Aziz, 2018), Islamic religious discourse (Bassiouney, 2013;Ismail, 2015;Stille, 2018;Susanto, 2006;Syam & Fitrawati, 2020;Triana & Eka Saputra, 2018), Christian discourse (Dladla, 2017), media (Octaviana, 2019;Silaban & Marpaung, 2020;Sutrisno & Ariesta, 2019), and leaders' discourse (Purba, 2017;Sugiantari, 2018;Wibowo et al, 2017).…”
Section: Background Of Studymentioning
confidence: 99%
“…The last was Zetri (2018) with the title "An analysis of code mixing in a debate activity as part of English club programs at SMAN 2 Bengkulu city". The result showed that there were two types of code mixing applied by the students in debate activities.…”
Section: Introductionmentioning
confidence: 99%